Anti-fingerprint screen protective film and preparation method thereof
By using antibacterial anti-fingerprint flame retardant layer composed of modified graphene oxide and other materials in the anti-fingerprint screen protector, and combined with the structural design of other layers, the problem of insufficient antibacterial and flame retardant performance in the prior art is solved, and efficient antibacterial, flame retardant, waterproof and wear resistance are achieved.
Patent Information
- Application Number
- CN202411917184.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
The antibacterial and flame retardant properties of the existing anti-fingerprint screen protector are relatively single and have not been effectively improved.
An anti-bacterial anti-fingerprint flame retardant layer consisting of polyurethane acrylate, nanosilicon dioxide, modified graphene oxide, diluent, photoinitiator and leveling agent is adopted, and a structural design of the substrate layer, pressure-sensitive adhesive layer and release layer is combined, and a conical depression array is formed by laser etching to enhance hydrophobic performance.
It realizes the efficient antibacterial, flame retardant, waterproof, oil stain and wear resistance of anti-fingerprint screen protector, while improving light transmittance and anti-aging properties.
Smart Images

Figure BDA0005207086360000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of screen protective films, and in particular relates to an anti-fingerprint screen protective film and a preparation method thereof. Background Art
[0002] With the development of modern economy and the improvement of communication technology, mobile phones have become a necessity in people's daily life. With the innovation of technology, the resolution, color performance and other performance of mobile phone screens are also constantly improving, giving people the most intuitive visual experience. Therefore, mobile phone screens are used more and more frequently. Due to the sweat and grease on people's hands, frequent use can easily leave fingerprints on the screen, thus affecting the viewing experience. In order to solve this problem, people have developed a variety of protective films with hydrophobic and oleophobic effects, which cover the screen to reduce the fingerprints left by people's hands when touching the screen.
[0003] The patent with the patent announcement number CN111690332B discloses a high-definition hydrophobic screen protective film and its use. The high-definition hydrophobic screen protective film provided by the patent has good light transmittance and hydrophobic properties, high wear resistance, and the hydrophobic coating can be used for a long time without falling off. It can be applied to computer monitors, car displays, mobile phone screens, tablet screens, wearable device displays, and smart home displays. However, the anti-fingerprint screen protective film obtained by the patent has a relatively single function, and its antibacterial and flame retardant properties need to be improved. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-fingerprint screen protective film and a preparation method thereof, aiming to solve the problem that the anti-fingerprint screen protective film prepared by the prior art in the background technology has a relatively single function and its antibacterial and flame retardant properties need to be improved.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] In the first aspect, an anti-fingerprint screen protective film comprises, from the outside to the inside, an antibacterial anti-fingerprint flame retardant layer, a substrate layer, a pressure-sensitive adhesive layer and a release layer, wherein the antibacterial anti-fingerprint flame retardant layer comprises the following raw materials by weight: 80-90 parts of polyurethane acrylate, 10-30 parts of nano-silicon dioxide, 4-8 parts of modified graphene oxide, 30-50 parts of diluent, 4-8 parts of photoinitiator, and 1-2 parts of leveling agent.
[0007] The modified graphene oxide is hyperbranched polysilane grafted graphene oxide, and the hyperbranched polysilane is obtained by hydrolysis and condensation of γ-glycidyloxypropyltrimethoxysilane, antibacterial and flame-retardant siloxane and antioxidant siloxane.
[0008] Nano-silicon dioxide has high hardness and can improve the wear resistance of the antibacterial, anti-fingerprint and flame-retardant layer, but nano-silicon dioxide has the disadvantage of poor dispersibility.
[0009] After the hyperbranched polysilane is modified with graphene oxide, due to its low viscosity, good organic compatibility and the fact that its epoxy group can also undergo a ring-opening reaction with the hydroxyl group on the surface of nano-silica, it can improve the interfacial strength between graphene oxide and nano-silica and other raw materials, and enhance the dispersibility of graphene oxide and nano-silica in the raw materials. The uniform dispersion of nano-silica also helps to form a more continuous waterproof layer and a harder protective layer, which can effectively improve the anti-fingerprint performance and wear resistance of the anti-fingerprint screen protective film; the uniform dispersion of modified graphene oxide can ensure the light transmittance of the protective film while also improving the wear resistance of the protective film. In addition, hyperbranched polysilane has a low surface energy, which can prevent stains and fingerprints from adhering to the surface of the mobile phone film, and can also resist the adhesion of bacteria, with excellent anti-fouling and anti-fingerprint capabilities.
[0010] Furthermore, a conical depression array is provided on the contact surface between the substrate layer and the high-definition hydrophobic layer, the cone diameter of the conical depression array is 15 μm, the depth is 15 μm, and the area of the conical depression array accounts for 6%.
[0011] The conical depression array enables the high-definition hydrophobic layer to form an anchoring structure at the interface between the two after solidification, thereby enhancing the bonding force.
[0012] Furthermore, the substrate layer is any one of PP material, PC material, PU material and PET material.
[0013] Furthermore, the pressure-sensitive adhesive layer is any one of acrylic pressure-sensitive adhesive, polyurethane pressure-sensitive adhesive, and silicone pressure-sensitive adhesive.
[0014] Furthermore, the release layer is made of PET material.
[0015] Furthermore, the thickness of the antibacterial and anti-fingerprint flame-retardant layer is 50 μm, the thickness of the substrate layer is 80 μm, the thickness of the pressure-sensitive adhesive layer is 30 μm, and the thickness of the release layer is 60 μm.
[0016] Furthermore, the diluent is polybutadiene; the photoinitiator is photoinitiator-1000; and the leveling agent is KMT-5510 leveling agent.
[0017] Furthermore, the preparation method of modified graphene oxide is:
[0018] Graphene oxide, acetic acid aqueous solution and tetrahydrofuran were added into a flask, the temperature was controlled at 70-75° C., a hyperbranched monomer was added, the reaction was kept warm for 24 hours, the flask was washed with distilled water and dried to obtain modified graphene oxide.
[0019] Among them, the mass ratio of graphene oxide, acetic acid aqueous solution, tetrahydrofuran and hyperbranched monomer is 0.2:1:(6-10):2, the mass fraction of acetic acid aqueous solution is 66.7%, and the hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane, antibacterial flame retardant siloxane and antioxidant siloxane in a mass ratio of 1:0.2-0.4:0.6-0.8.
[0020] The reaction mechanism of the above reaction is: the methoxy and ethoxy groups in the hyperbranched monomer are hydrolyzed to generate silanols, which are then bonded to the hydroxyl groups on the surface of graphene oxide through hydrogen bonds, and finally dehydrated and condensed. The remaining hydroxyl groups on the silanols are dehydrated and condensed with the silanols generated by the hydrolysis of the hyperbranched monomers. The dehydration and condensation reactions are repeated to eventually form a hyperbranched structure and obtain modified graphene oxide.
[0021] Furthermore, the preparation method of the antibacterial flame retardant siloxane is:
[0022] 11-Azidoundecyltrimethoxysilane and sodium propargyl sulfonate are added to anhydrous DMF, stirred, copper acetate and triphenylphosphine are added, reacted at room temperature for 3-5 hours, saturated ammonium chloride solution is added, then ethyl acetate and water are added, and the mixture is allowed to stand for stratification. The obtained organic phase is washed and dried to obtain antibacterial flame-retardant siloxane.
[0023] Among them, the usage ratio of 11-azidoundecyltrimethoxysilane, sodium propargyl sulfonate, anhydrous DMF, cupric acetate and triphenylphosphine is 12.7g:5.7g:200mL:0.8g:2.1g.
[0024] The azide group in 11-azidoundecyltrimethoxysilane and the alkynyl group in sodium propargyl sulfonate undergo an azide-alkynyl cycloaddition reaction, and copper acetate is used as a catalyst to catalyze the above reaction to obtain an antibacterial flame-retardant siloxane, which contains a triazole ring and N, S, and Si flame-retardant elements. The triazole ring has antibacterial properties and can improve the antibacterial properties of the protective film. The siloxane monomer containing the triazole ring can condense with other monomers to form a hyperbranched polysilane, so that the antibacterial group is not easy to precipitate, and a long-lasting antibacterial effect can be achieved. Elements such as N, S, and Si work together to improve the flame retardant properties of the protective film through mechanisms such as generating non-flammable gas, diluting oxygen concentration, forming a protective carbon layer, and isolating oxygen.
[0025] Furthermore, the preparation method of the antioxidant siloxane is:
[0026] 3-Aminopropyltriethoxysilane was placed in anhydrous DMF, stirred for 1-2 hours, and then nitrogen was introduced to deoxygenate. Sinapic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added, and the mixture was reacted at 140° C. for 6-8 hours. After cooling to room temperature, the mixture was filtered, washed and dried to obtain an antioxidant siloxane.
[0027] Among them, the usage ratio of 3-aminopropyltriethoxysilane, anhydrous DMF, sinapinic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 2.9g:70mL:3g:0.6g:0.4g.
[0028] The amino group of 3-aminopropyltriethoxysilane reacts with the carboxyl group of mustard acid to obtain an antioxidant siloxane. Sinaccic acid can remove free radicals and block the oxidation reaction chain, and has an excellent antioxidant effect. After being bonded with 3-aminopropyltriethoxysilane, the monomer can condense with other monomers to form a hyperbranched polysilane, so that the mustard acid is fixed in the hyperbranched structure, so that the small molecule antioxidant will not precipitate even when the protective film is used for a long time, and it can exert a long-term antioxidant effect, prevent the protective film from being oxidized and yellowing, and increase the service life of the protective film for mobile phone screens.
[0029] In a second aspect, a method for preparing an anti-fingerprint screen protective film comprises the following steps:
[0030] B1: Put the polyurethane acrylate, photoinitiator and leveling agent in the formula ratio into a mixer, stir at a high speed of 300-400rpm for 30-60min to obtain a polymer component A; ultrasonically disperse the diluent, nano-silicon dioxide and modified graphene oxide in the formula ratio for 30-60min to obtain a modified component B; then slowly add the modified component B to the polymer component A, stir at a speed of 200-300rpm for 15-30min to obtain an antibacterial and anti-fingerprint flame retardant adhesive;
[0031] B2: After the film substrate is corona treated, it is coated with a pressure-sensitive adhesive by a coater, and then put into an oven for curing at a temperature of 60-120°C for a time of 10-30 minutes. After the curing is completed, a release film is compounded to obtain an intermediate film having a substrate layer, a pressure-sensitive adhesive layer and a release layer structure;
[0032] B3: The surface of the substrate layer of the intermediate film obtained in step B2 is etched by laser etching. By controlling the laser power and angle, a conical depression array is etched on the surface of the substrate layer of the intermediate film; then the antibacterial and anti-fingerprint flame retardant adhesive prepared in step B1 is coated on the surface of the substrate layer, and cured by UV light source, and the radiation energy is controlled at 3000-4000mJ / cm 2 , an anti-fingerprint screen protective film is produced.
[0033] Beneficial effects of the present invention:
[0034] 1. The present invention prepares modified graphene oxide and participates in the preparation process of the antibacterial and anti-fingerprint flame retardant layer to obtain an anti-fingerprint screen protective film, so that the prepared anti-fingerprint screen protective film has an antibacterial rate of more than 99.91%, an oxygen index LOI of more than 42.1%, ink traces can fade quickly, a water contact angle of more than 120°, a light transmittance of more than 93.4%, and excellent anti-aging and wear resistance. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The graphene oxide film in the present invention was purchased from Nanjing Pioneer Nano Co., Ltd., item number: 100027, CAS number: 7440-44-0, parameters: size: 9x9cm thickness: about 25 microns;
[0037] Nano-silicon dioxide was purchased from Hangzhou Wanjing New Materials Co., Ltd. The average particle size of nano-silicon dioxide was 30 mm and the specific surface area was 220 m 2 / g, and the apparent density is 55g / L.
[0038] Preparation Example 1
[0039] The preparation method of the modified graphene oxide in this preparation example is:
[0040] 0.2g of graphene oxide, 1g of 66.7% acetic acid aqueous solution, and 6g of tetrahydrofuran were added to a flask, the temperature was controlled at 70°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and dried to obtain modified graphene oxide. The hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane, antibacterial flame retardant siloxane, and antioxidant siloxane in a mass ratio of 1:0.2:0.8.
[0041] The preparation method of antibacterial flame retardant siloxane is:
[0042] 12.7 g of 11-azidoundecyltrimethoxysilane and 5.7 g of sodium propargyl sulfonate were added to 200 mL of anhydrous DMF and stirred. 0.8 g of cupric acetate and 2.1 g of triphenylphosphine were added and reacted at room temperature for 3 h. A saturated ammonium chloride solution was added, followed by ethyl acetate and water. The mixture was allowed to stand for stratification. The obtained organic phase was washed and dried to obtain an antibacterial flame-retardant siloxane.
[0043] The preparation method of antioxidant siloxane is:
[0044] 2.9 g of 3-aminopropyltriethoxysilane was placed in 70 mL of anhydrous DMF, stirred for 1 h, and then nitrogen was introduced for deoxygenation. 3 g of sinapinic acid, 0.6 g of dicyclohexylcarbodiimide and 0.4 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 140 ° C for 6 h. After cooling to room temperature, it was filtered, washed and dried to obtain an antioxidant siloxane.
[0045] Preparation Example 2
[0046] The preparation method of the modified graphene oxide in this preparation example is:
[0047] 0.2g of graphene oxide, 1g of 66.7% acetic acid aqueous solution, and 6g of tetrahydrofuran were added to a flask, the temperature was controlled at 75°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and dried to obtain modified graphene oxide. The hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane, antibacterial flame retardant siloxane and antioxidant siloxane in a mass ratio of 1:0.4:0.6.
[0048] The preparation method of antibacterial flame retardant siloxane is:
[0049] 12.7 g of 11-azidoundecyltrimethoxysilane and 5.7 g of sodium propargyl sulfonate were added to 200 mL of anhydrous DMF and stirred. 0.8 g of cupric acetate and 2.1 g of triphenylphosphine were added and reacted at room temperature for 5 h. A saturated ammonium chloride solution was added, followed by ethyl acetate and water. The mixture was allowed to stand for stratification. The obtained organic phase was washed and dried to obtain an antibacterial flame-retardant siloxane.
[0050] The preparation method of antioxidant siloxane is:
[0051] 2.9 g of 3-aminopropyltriethoxysilane was placed in 70 mL of anhydrous DMF, stirred for 2 h, and then nitrogen was introduced for deoxygenation. 3 g of sinapinic acid, 0.6 g of dicyclohexylcarbodiimide and 0.4 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 140 ° C for 8 h. After cooling to room temperature, it was filtered, washed and dried to obtain an antioxidant siloxane.
[0052] Comparative Example 1
[0053] The preparation method of modified graphene oxide in this comparative example is:
[0054] 0.2g of graphene oxide, 1g of 66.7% acetic acid aqueous solution, and 6g of tetrahydrofuran were added to a flask, the temperature was controlled at 70°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and dried to obtain modified graphene oxide. The hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane and antibacterial flame retardant siloxane in a mass ratio of 1:1.
[0055] Comparative Example 2
[0056] The preparation method of modified graphene oxide in this comparative example is:
[0057] 0.2g of graphene oxide, 1g of 66.7% acetic acid aqueous solution, and 6g of tetrahydrofuran were added to a flask, the temperature was controlled at 70°C, 2g of hyperbranched monomer was added, the reaction was kept warm for 24h, washed with distilled water, and dried to obtain modified graphene oxide. The hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane and antioxidant siloxane in a mass ratio of 1:1.
[0058] Comparative Example 3
[0059] The preparation method of modified graphene oxide in this comparative example is:
[0060] 0.2g of graphene oxide, 1g of 66.7% acetic acid aqueous solution, and 6g of tetrahydrofuran were added to a flask, the temperature was controlled at 70°C, 2g of a hyperbranched monomer was added, the reaction was kept warm for 24h, the mixture was washed with distilled water, and dried to obtain modified graphene oxide. The hyperbranched monomer was γ-glycidyloxypropyltrimethoxysilane.
[0061] Comparative Example 4
[0062] The preparation method of modified graphene oxide in this comparative example is:
[0063] 0.2 g of graphene oxide, 1 g of 66.7% acetic acid aqueous solution, and 6 g of tetrahydrofuran were added into a flask, the temperature was controlled at 70° C., 0.02 g of γ-glycidyloxypropyltrimethoxysilane was added, the reaction was kept warm for 24 h, the mixture was washed with distilled water, and dried to obtain modified graphene oxide.
[0064] Comparative Example 5
[0065] This comparative example directly uses graphene oxide.
[0066] Example 1
[0067] An anti-fingerprint screen protective film, the film from the outside to the inside are respectively an antibacterial anti-fingerprint flame retardant layer, a substrate layer, a pressure-sensitive adhesive layer and a release layer, the antibacterial anti-fingerprint flame retardant layer comprises the following raw materials by weight: 90 parts of polyurethane acrylate, 10 parts of nano-silicon dioxide, 4 parts of modified graphene oxide prepared in Preparation Example 1, 50 parts of polybutadiene, 8 parts of photoinitiator-1000, and 2 parts of KMT-5510 leveling agent. The thickness of the antibacterial anti-fingerprint flame retardant layer is 50 μm
[0068] A conical depression array is provided on the contact surface between the substrate layer and the high-definition hydrophobic layer. The cone diameter of the conical depression array is 15 μm, the depth is 15 μm, and the area of the conical depression array accounts for 6%.
[0069] The substrate layer is made of PP material with a thickness of 80μm.
[0070] The pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive with a thickness of 30 μm.
[0071] The release layer is made of PET and has a thickness of 60μm.
[0072] The method for preparing the anti-fingerprint screen protective film comprises the following steps:
[0073] B1: Put the polyurethane acrylate, photoinitiator and leveling agent in the formula ratio into a mixer, stir at a high speed of 300 rpm for 30 minutes to obtain a polymer component A; ultrasonically disperse the diluent, nano-silicon dioxide and modified graphene oxide in the formula ratio for 30 minutes to obtain a modified component B; then slowly add the modified component B to the polymer component A, stir at a speed of 200 rpm for 15 minutes to obtain an antibacterial and anti-fingerprint flame retardant adhesive;
[0074] B2: After the film substrate is corona treated, it is coated with a pressure-sensitive adhesive by a coater and then put into an oven for curing at a temperature of 60°C for 10 minutes. After the curing is completed, a release film is compounded to obtain an intermediate film having a substrate layer, a pressure-sensitive adhesive layer and a release layer structure;
[0075] B3: The surface of the substrate layer of the intermediate film obtained in step B2 is etched by laser etching. By controlling the laser power and angle, a conical depression array is etched on the surface of the substrate layer of the intermediate film; then the antibacterial and anti-fingerprint flame retardant adhesive prepared in step B1 is coated on the surface of the substrate layer, and cured by UV light source, and the radiation energy is controlled at 3000mJ / cm 2 , an anti-fingerprint screen protective film is produced.
[0076] Example 2
[0077] An anti-fingerprint screen protective film, the film from the outside to the inside are respectively an antibacterial anti-fingerprint flame retardant layer, a substrate layer, a pressure-sensitive adhesive layer and a release layer, the antibacterial anti-fingerprint flame retardant layer comprises the following raw materials by weight: 85 parts of polyurethane acrylate, 20 parts of nano-silicon dioxide, 6 parts of modified graphene oxide prepared in Preparation Example 2, 40 parts of polybutadiene, 6 parts of photoinitiator-1000, and 1.5 parts of KMT-5510 leveling agent. The thickness of the antibacterial anti-fingerprint flame retardant layer is 50 μm
[0078] A conical depression array is provided on the contact surface between the substrate layer and the high-definition hydrophobic layer. The cone diameter of the conical depression array is 15 μm, the depth is 15 μm, and the area of the conical depression array accounts for 6%.
[0079] The substrate layer is made of PC material and has a thickness of 80 μm.
[0080] The pressure-sensitive adhesive layer is polyurethane pressure-sensitive adhesive with a thickness of 30 μm.
[0081] The release layer is made of PET and has a thickness of 60μm.
[0082] The method for preparing the anti-fingerprint screen protective film comprises the following steps:
[0083] B1: Put the polyurethane acrylate, photoinitiator and leveling agent in the formula ratio into a mixer, stir at a speed of 400 rpm for 60 minutes to obtain a polymer component A; ultrasonically disperse the diluent, nano-silicon dioxide and modified graphene oxide in the formula ratio for 60 minutes to obtain a modified component B; then slowly add the modified component B to the polymer component A, stir at a speed of 300 rpm for 30 minutes to obtain an antibacterial and anti-fingerprint flame retardant adhesive;
[0084] B2: After the film substrate is corona treated, it is coated with a pressure-sensitive adhesive by a coater and then put into an oven for curing at a temperature of 120°C for 30 minutes. After the curing is completed, a release film is compounded to obtain an intermediate film having a substrate layer, a pressure-sensitive adhesive layer and a release layer structure;
[0085] B3: The surface of the substrate layer of the intermediate film obtained in step B2 is etched by laser etching. By controlling the laser power and angle, a conical depression array is etched on the surface of the substrate layer of the intermediate film; then the antibacterial and anti-fingerprint flame retardant adhesive prepared in step B1 is coated on the surface of the substrate layer, and cured by UV light source, and the radiation energy is controlled at 4000mJ / cm 2 , an anti-fingerprint screen protective film is produced.
[0086] Example 3
[0087] An anti-fingerprint screen protective film, the film from the outside to the inside are respectively an antibacterial anti-fingerprint flame retardant layer, a substrate layer, a pressure-sensitive adhesive layer and a release layer, the antibacterial anti-fingerprint flame retardant layer comprises the following raw materials by weight: 80 parts of polyurethane acrylate, 30 parts of nano-silicon dioxide, 8 parts of modified graphene oxide prepared in Preparation Example 2, 30 parts of polybutadiene, 4 parts of photoinitiator-1000, and 1 part of KMT-5510 leveling agent. The thickness of the antibacterial anti-fingerprint flame retardant layer is 50 μm
[0088] A conical depression array is provided on the contact surface between the substrate layer and the high-definition hydrophobic layer. The cone diameter of the conical depression array is 15 μm, the depth is 15 μm, and the area of the conical depression array accounts for 6%.
[0089] The substrate layer is made of PET and has a thickness of 80 μm.
[0090] The pressure-sensitive adhesive layer is a silicone pressure-sensitive adhesive with a thickness of 30 μm.
[0091] The release layer is made of PET and has a thickness of 60μm.
[0092] The method for preparing the anti-fingerprint screen protective film comprises the following steps:
[0093] B1: Put the polyurethane acrylate, photoinitiator and leveling agent in the formula ratio into a mixer, stir at a high speed of 350 rpm for 45 minutes to obtain a polymer component A; ultrasonically disperse the diluent, nano-silicon dioxide and modified graphene oxide in the formula ratio for 45 minutes to obtain a modified component B; then slowly add the modified component B to the polymer component A, stir at a speed of 250 rpm for 23 minutes to obtain an antibacterial and anti-fingerprint flame retardant adhesive;
[0094] B2: After the film substrate is corona treated, it is coated with a pressure-sensitive adhesive by a coater and then put into an oven for curing at a temperature of 90°C for 20 minutes. After the curing is completed, a release film is compounded to obtain an intermediate film having a substrate layer, a pressure-sensitive adhesive layer and a release layer structure;
[0095] B3: The surface of the substrate layer of the intermediate film obtained in step B2 is etched by laser etching. By controlling the laser power and angle, a conical depression array is etched on the surface of the substrate layer of the intermediate film; then the antibacterial and anti-fingerprint flame retardant adhesive prepared in step B1 is coated on the surface of the substrate layer, and cured by UV light source, and the radiation energy is controlled at 3500mJ / cm 2 , an anti-fingerprint screen protective film is produced.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 1 is that the modified graphene oxide prepared in Preparation Example 1 in Example 1 is replaced by the product prepared in Control Example 1, and the remaining raw materials and steps are the same as in Example 1.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 1 is that the modified graphene oxide prepared in Preparation Example 1 in Example 1 is replaced by the product prepared in Control Example 2, and the remaining raw materials and steps are the same as in Example 1.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 1 is that the modified graphene oxide prepared in Preparation Example 1 in Example 1 is replaced by the product prepared in Control Example 3, and the other raw materials and steps are the same as in Example 1.
[0102] Comparative Example 4
[0103] This comparative example is compared with Example 1, except that the modified graphene oxide prepared in Preparation Example 1 in Example 1 is replaced by the product prepared in Control Example 4, and the remaining raw materials and steps are the same as in Example 1.
[0104] Comparative Example 5
[0105] This comparative example is compared with Example 1, except that the modified graphene oxide prepared in Preparation Example 1 in Example 1 is replaced by the product prepared in Control Example 5, and the remaining raw materials and steps are the same as in Example 1.
[0106] The anti-fingerprint screen protective films prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to performance tests, and the test items are as follows. The results are shown in Table 1:
[0107] 1. Antibacterial test: 1mL of 10 -5 CFU / mL of Staphylococcus aureus solution was added dropwise to the sterilized sample surface and cultured at 37°C for 8 h. 20 μL of the cultured solution was transferred and evenly spread on the solid culture medium. After cultured at 37°C for 24 h, the number of colonies on the culture medium was counted and a blank experiment was performed at the same time. The antibacterial rate (%) = (AB) / A×100%, where A is the number of colonies on the culture medium counted in the blank experiment; and B is the number of colonies on the culture medium counted in the sample group experiment.
[0108] 2. Flame retardancy test: The oxygen index LO I value is tested according to GB / T 2406.2-2009 standard.
[0109] 3. Anti-fouling oil pen test: Use a Hi-Mckee (ZEBRA) oil pen to draw a line on the coating sample, and then carefully observe the changes in the ink mark.
[0110] 4. Hydrophobicity test: Use JC2000D2G contact angle tester to test the water contact angle of the sample.
[0111] 5. Light transmittance test: Test according to the method of GB / T2410-2008.
[0112] 6. Antioxidant performance: Use XH8650 universal tensile test machine to test the tensile strength of samples before aging treatment and samples after being treated in 100℃ aging box for 2 days. The effective length of the test is 100nm, the test speed is 10mm / min, and the tensile strength retention rate is calculated.
[0113] 7. Wear resistance: Stick the sample on the sample table of GSL-46 steel wool friction resistance testing machine, place 500g and 1000g load weights on the top respectively, rub the sample back and forth, repeat 50 cycles at a speed of 15mm / s, and observe the scratches on the sample surface.
[0114] Table 1
[0115]
[0116]
[0117] As can be seen from Table 1, the anti-fingerprint protective films prepared in Examples 1 to 3 have excellent antibacterial properties, flame retardant properties, waterproof and oil-resistant properties, wear resistance, and anti-aging properties. Comparative Example 1 does not contain antioxidant siloxane, and its anti-aging properties are poorer than those of Example 1; Comparative Example 2 does not contain antibacterial and flame-retardant siloxane, and its antibacterial and flame-retardant properties are lower than those of Example 1; Comparative Example 3 does not contain antioxidant siloxane and antibacterial and flame-retardant siloxane, and its antibacterial, flame-retardant, and anti-aging properties are all lower than those of Example 1; Comparative Example 4 does not have a hyperbranched structure, and its comprehensive properties are poorer than those of Example 1; Comparative Example 5 directly uses graphene oxide, and its comprehensive properties are the worst compared to other comparative examples.
[0118] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-fingerprint screen protective film, characterized in that: The film comprises an antibacterial anti-fingerprint flame retardant layer, a substrate layer, a pressure-sensitive adhesive layer and a release layer from the outside to the inside. The antibacterial anti-fingerprint flame retardant layer comprises the following raw materials by weight: 80-90 parts of polyurethane acrylate, 10-30 parts of nano silicon dioxide, 4-8 parts of modified graphene oxide, 30-50 parts of diluent, 4-8 parts of photoinitiator and 1-2 parts of leveling agent. The modified graphene oxide is hyperbranched polysilane grafted graphene oxide, and the hyperbranched polysilane is obtained by hydrolysis and condensation of γ-glycidyloxypropyltrimethoxysilane, antibacterial and flame-retardant siloxane and antioxidant siloxane.
2. The anti-fingerprint screen protective film according to claim 1, characterized in that: A conical depression array is provided on the contact surface between the substrate layer and the high-definition hydrophobic layer. The cone diameter of the conical depression array is 15 μm, the depth is 15 μm, and the area of the conical depression array accounts for 6%.
3. The anti-fingerprint screen protective film according to claim 1, characterized in that: The substrate layer is any one of PP material, PC material, PU material, and PET material; the pressure-sensitive adhesive layer is any one of acrylic pressure-sensitive adhesive, polyurethane pressure-sensitive adhesive, and silicone pressure-sensitive adhesive; and the release layer is made of PET material.
4. The anti-fingerprint screen protective film according to claim 1, characterized in that: The thickness of the antibacterial and anti-fingerprint flame-retardant layer is 50 μm, the thickness of the substrate layer is 80 μm, the thickness of the pressure-sensitive adhesive layer is 30 μm, and the thickness of the release layer is 60 μm.
5. The anti-fingerprint screen protective film according to claim 1, characterized in that: The diluent is polybutadiene; the photoinitiator is photoinitiator-1000; and the leveling agent is KMT-5510 leveling agent.
6. The anti-fingerprint screen protective film according to claim 1, characterized in that: The preparation method of modified graphene oxide is: Graphene oxide, acetic acid aqueous solution and tetrahydrofuran were added into a flask, the temperature was controlled at 70-75° C., a hyperbranched monomer was added, the reaction was kept warm for 24 hours, the flask was washed with distilled water and dried to obtain modified graphene oxide.
7. The anti-fingerprint screen protective film according to claim 6, characterized in that: The mass ratio of graphene oxide, acetic acid aqueous solution, tetrahydrofuran and hyperbranched monomer is 0.2:1:(6-10):2, the mass fraction of acetic acid aqueous solution is 66.7%, and the hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane, antibacterial flame retardant siloxane and antioxidant siloxane in a mass ratio of 1:0.2-0.4:0.6-0.
8.
8. The anti-fingerprint screen protective film according to claim 7, characterized in that: The preparation method of antibacterial flame retardant siloxane is: 11-azidoundecyltrimethoxysilane and sodium propargyl sulfonate are added to anhydrous DMF, stirred, copper acetate and triphenylphosphine are added, reacted at room temperature for 3-5 hours, saturated ammonium chloride solution is added, then ethyl acetate and water are added, and the mixture is allowed to stand for stratification, and the obtained organic phase is washed and dried to obtain an antibacterial flame retardant siloxane; Among them, the usage ratio of 11-azidoundecyltrimethoxysilane, sodium propargyl sulfonate, anhydrous DMF, cupric acetate and triphenylphosphine is 12.7g:5.7g:200mL:0.8g:2.1g.
9. The anti-fingerprint screen protective film according to claim 7, characterized in that: The preparation method of antioxidant siloxane is: 3-aminopropyltriethoxysilane was placed in anhydrous DMF, stirred for 1-2 hours, and then nitrogen was introduced to deoxygenate, and sinapinic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added, and the mixture was reacted at 140° C. for 6-8 hours. After cooling to room temperature, the mixture was filtered, washed and dried to obtain an antioxidant siloxane; Among them, the usage ratio of 3-aminopropyltriethoxysilane, anhydrous DMF, sinapinic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 2.9g:70mL:3g:0.6g:0.4g.
10. The method for preparing an anti-fingerprint screen protective film according to any one of claims 1 to 9, characterized in that: The following steps are involved: B1: Put the polyurethane acrylate, photoinitiator and leveling agent in the formula ratio into a mixer, stir at a high speed of 300-400rpm for 30-60min to obtain a polymer component A; ultrasonically disperse the diluent, nano-silicon dioxide and modified graphene oxide in the formula ratio for 30-60min to obtain a modified component B; then slowly add the modified component B to the polymer component A, stir at a speed of 200-300rpm for 15-30min to obtain an antibacterial and anti-fingerprint flame retardant adhesive; B2: After the film substrate is corona treated, it is coated with a pressure-sensitive adhesive by a coater, and then put into an oven for curing at a temperature of 60-120°C for a time of 10-30 minutes. After the curing is completed, a release film is compounded to obtain an intermediate film having a substrate layer, a pressure-sensitive adhesive layer and a release layer structure; B3: using a laser etching method to etch the surface of the substrate layer of the intermediate film obtained in step B2, and by controlling the laser power and angle, etching a conical depression array on the surface of the substrate layer of the intermediate film; Then the antibacterial and anti-fingerprint flame retardant adhesive prepared in step B1 is coated on the surface of the substrate layer and cured by UV light source, with the radiation energy controlled at 3000-4000mJ / cm 2 , an anti-fingerprint screen protective film is produced.
Citation Information
Patent Citations
A high-definition hydrophobic screen protector and its applications
CN111690332B
Cited By
Conductive unsaturated polyester resin and preparation method thereof
CN119978753A
High-temperature-resistant waterproof PET label and preparation process thereof
CN120564523A